Examining the determine of self efficacy, social conditions, and scientific literacy based on PISA Test like: An in-vitro study - D S Pratama; T I Hartini; A Kusdiwelirawan (Pascasarjana Universitas Pendidikan Indonesia, 2018)
This study is aimed to determine the students achievment of scientific literacy with social condition as an independent variable and self efficacy as an interventing variable according as an in-vitro study. This research consist to used quantitative descriptive method and this study is applied on 56 students who are educated at the first grade of SMK Avicena Rajeg in academic years of 2017/2018. The instrument used was a scientific literacy test based on PISA test-like and social condition and self efficacy was a questionnare. The result of this study showed that the residual regression analysis value of social condition and self efficacy was 0.941, the residual regression analysis value of social condition and self efficacy to scientific literacy was 0.932. The direct influence of exogenous variables in the form of social conditions on endogenous variables is 11.61%, and the effect of self efficacy as an interventing variable is 9.24%. This value was considered means social conditions have a positive effect directly or through the self efficacy of students at the first grade of SMK Avicena Rajeg.